Cardiac function, myocardial mechano-energetic efficiency, and ventricular–arterial coupling in normal pregnancy. Issue 4 (April 2018) - Iacobaeus, Charlotte; Andolf, Ellika; Thorsell, Malin; Bremme, Katarina; Östlund, Eva; Kahan, Thomas
Abstract : Objective: To assess cardiac function, myocardial mechanoenergetic efficiency (MEE), and ventricular–arterial coupling (VAC) longitudinally during normal pregnancy, and to study if there was an association between cardiac structure and function, and fetal growth. Methods: Cardiac structure and function, MEE, and ventricular–arterial coupling was assessed longitudinally in 52 healthy nulliparous women at 14, 24, and 34 weeks' gestation and 9-month postpartum. Results: Left atrial diameter increased during pregnancy (30.41 ± 3.59 mm in the nonpregnant state and 31.02 ± 3.91, 34.06 ± 3.58, and 33.9 ± 2.97 mm in the first, second, and third trimesters, P  < 0.001). Left ventricular mass increased 117.12 ± 45.0 g in the nonpregnant state and 116.5 ± 33.0, 126.9 ± 34.5, 128.4 ± 36 g in the first, second, and third trimesters ( P  < 0.001). Cardiac output increased from 3.4 ± 1.2 l/min to 4.3 ± 0.7 l/min in the second and third trimesters ( P  < 0.001). Diastolic function decreased as both E / A and e′ / a′ decreased during pregnancy ( P  < 0.05 and P  < 0.001, respectively). MEE and VAC were retained during pregnancy. Heart rate was associated with birth weight centile in the first ( r  = 0.41, P  = 0.002) and second ( r  = 0.46, P  = 0.002) trimester. Conclusion: The increase in cardiac output during normal pregnancy is obtained by an increase in heart rate, followed by structural cardiac changes. The impaired systolic function is accomplished by a deteriorated diastolic function. Despite these rapid changes, the myocardium manages to work efficient with a preserved MEE. Cardiac and arterial adaption to pregnancy seems to appear parallel as evidenced by a preserved VAC. Abstract : Supplemental Digital Content is available in the text